When do abusive leaders experience guilt?. Issue 6 (2nd January 2020) - Shum, Cass; Gatling, Anthony; Tu, Min-Hsuan
Abstract : Purpose: Drawing from the appraisal theory, this paper aims to examine the conditions under which abusive leaders experience guilt and suggests that guilt motivates leaders to help followers. Design/methodology/approach: A scenario study with a sample of 285 hospitality supervisors was used to test the theoretical model. Path analyses were conducted to test the three-way-moderated mediation model. Findings: Results show a three-way interaction among enacted abuse, managerial abuse and agreeableness on the guilt: leaders are more likely to experience guilt over their enacted abusive supervision when they do not perceive their direct manager as abusive and when they are agreeable. Moreover, guilt mediates the relationship between enacted abuse and a leader's intention to help their followers. Research limitations/implications: This study shows that abusive supervisors pay an emotional cost for their enacted abuse (in terms of guilt). Practical implications: Hospitality organization should assign non-abusive mentors to leaders, especially agreeable ones, to detect and reduce abusive supervision. Originality/value: First, this study addressed the lack of research on the effect of abusive supervision on the abusers by studying the conditions under which abusive leaders experience guilt. Second, this study shows that because of guilt, abusive leaders have a higher intention to help their followers. It explains why abusive leaders can be helpful.